ANALISIS HASIL SUPERVISI AKADEMIK GURU SEKOLAH MENENGAH PERTAMA DI PURWOREJO, JAWA TENGAH - Suwito, Suwito; Putut, Hartono; Choirul, Huda (STKIP Pesisir Selatan, 2017)
An observational study of teachers at SMPN 36 Purworejo Central Java has been conducted. The purpose of this supervision observation is to evaluate teachers based on pedagogical, personality, social, and professional competence. Academic supervision activities include several stages, namely: preparation of academic supervision, supervision implementation, supervision evaluation, and follow-up supervision. Of the 7 samples of supervised teachers, the average score of pedagogic competence was 91.7%, the average personality competence was 94.4%, the average of social competence was 87.5%, and the average professional competence was 94.4 %. Meanwhile, if viewed individually, got the percentage of teacher acquisition for all competence for teacher A equal to 82,14%, teacher B, C and D get value equal to 87,5%, teacher E equal to 100% and teacher F have value 96,43% . From the results of supervision analysis, it was found that almost all teachers get good results with an average value of 3.5 or average achievement score of all teachers supervised is 90.18%. However, many teachers still have weaknesses in the management of learning both in the search for methods and learning tools. Follow-up from the academic supervision results include the need for a workshop on making learning media, need to hold Traning Motivation for teachers, as well as the need for teachers to be sent to the MGMP Kabupaten activities for specific training methods or learning strategies.